2012
DOI: 10.1111/j.1399-5618.2012.01029.x
|View full text |Cite
|
Sign up to set email alerts
|

Will disruptive mood dysregulation disorder reduce false diagnosis of bipolar disorder in children?

Abstract: Although DMDD does decrease the rate of diagnosis of bipolar disorder in children, how much depends on whether history or observation is used.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
44
0
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(49 citation statements)
references
References 37 publications
4
44
0
1
Order By: Relevance
“…This attests to variable parental responses depending upon how the question was asked and how the question was understood. We have reported elsewhere that it is more difficult to obtain reliability on irritability (j = 0.72) than on subsequent explosive response (j = 1.0) even between professionals observing the child in the same setting (Margulies et al 2012). These data suggest that in exploring the important concept of irritability, we may need to do more basic work in measurement of responses.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…This attests to variable parental responses depending upon how the question was asked and how the question was understood. We have reported elsewhere that it is more difficult to obtain reliability on irritability (j = 0.72) than on subsequent explosive response (j = 1.0) even between professionals observing the child in the same setting (Margulies et al 2012). These data suggest that in exploring the important concept of irritability, we may need to do more basic work in measurement of responses.…”
Section: Discussionmentioning
confidence: 90%
“…Margulies et al (2012) found that 76.2% of inpatient children with severe outbursts were also rated by the staff as ''irritable'' during hospitalization. However, compiling all available information, DMDD was diagnosed in only 17.4% of these patients.…”
mentioning
confidence: 99%
“…In clinical practice, children with outbursts typically receive disruptive behavior diagnoses such as oppositional defiant disorder (ODD), attentiondeficit/hyperactivity disorder (ADHD) (Carlson and Dyson 2012;Margulies et al 2012), and conduct disorder ). In recent years, greater focus has been placed on severe tantrums as symptoms of a mood disturbance.…”
mentioning
confidence: 99%
“…(DSM-V) (American Psychiatric Association 2013). However, a recent study showed that only half of inpatient children (ages 5-12 years) with chronic irritability and explosiveness met criteria for DMDD (Margulies et al 2012).…”
mentioning
confidence: 99%
“…Comorbidity with ADHD and disruptive mood dysregulation disorders (DMDD) is very common in children and adolescents [2]. It is little known how DMDD symptoms affect ADHD treatment.…”
Section: Introductionmentioning
confidence: 99%